EX-SITU PREPARED NAFION–IONIC LIQUID COATED MERCURY FILM ELECTRODE FOR ADSORPTIVE STRIPPING VOLTAMMETRY OF LEAD IN THE PRESENCE OF AMARANTH - Nagles, Edgar Orlando; Arancibia, Verónica (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Nafion combined with ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM]F3MSO3) coated with mercury film (NLIHgFE) on a glassy carbon electrode modified allow the determine Pb(II) by adsorptive stripping voltammetry in the presence of Amaranth (Am). Properties of the NLIHgFE were characterized by square wave without and in the presence of other ionic liquid´s with different anion where ([EMIM]F3MSO3) showed to be more convenient in the determination the lead compared with other ionics liquids with smaller anions. pH 2.6 with buffer Britton-Robinson the complex Am-Pb was accumulated by adsorption on surface of the working electrode at -0.3 V by 80 s. and later reduce at negative potential by square wave and current peak appeared at -0.51 V earmarked to the reduction of lead in the complex. The linear calibration curves with ranged from 0.9–12.0 µgL–1 for Pb(II). The detection limits (3s) were estimated to be around 0.4 µgL–1 to Pb(II) . The relative standard deviations were 2.0 % at the 4.9 µg L–1 level of Pb(II) with 80 s of accumulation (n=7). Other optimal conditions were (CAm 0.77 µmol L–1; Eads –0.3 V; Frecuency 15 Hz and Amplitud pulse 25 mV). The methods were validated using reference material waste waters (SPS–WW1). Finally, the method was successfully applied to the determination of Pb(II) in tap water after UV digestion.